Utilising Injection Logging Tool: A Case Study of a Well in An Iraqi Oil Field - Saleh, Arafat T.; Al-Jawad, Mohammed S. (Iraqi Journal of Science, 2024)
Injection logging tools (ILT) have long been used in the industry to evaluate well performance and make strategic decisions. This case study validates the application of ILT in diagnosing anomalies and evaluating well-injection performance. An injector in Iraq's southern oil fields has three perforations, each in a different zone (commingled injection). Throughout the ILT job interpretation, at the flow pass analysis, according to the spinner recording, the first zone perforation takes all the injected water confirmed by the temperature sensor. While in the shut-in pass, the temperature sensor detects an anomaly, a cooling effect, on the entire first zone, not just in front of the injection perforation; there is also a cooling effect across the last perforation that is supposed to take nothing based on the spinner record at the flowing pass. Considering the interpretation, the whole first zone was connected vertically, with good rock quality, which made it cold by the effect of injected water. Also, a small amount of injected water goes to the other perforation, less than the value the spinner can detect. The downhole profile confirmed the perforations contribution.